Study on the factor that contribute to the financial problems of abandoned housing project in Malaysia - Nuramalina, Nuramalina (2017)
Abandoned buildings is one of the issues that are becoming the norm for local communities, but this issue is too often to be the subject of debate in the social media users and often featured in the House of Commons, Parliament. Although the era of development in Malaysia is increasing as well as high quality, but problems like this often happen. According to the official site of the National Housing Department, abandoned projects are defined as projects which meet the following criteria, which projects are not completed within or outside of the Sale and Purchase Agreement and no significant activity on the construction site during the six (6) months of continuous service; or winding-up petition has been filed in the High Court under Section 218 of the Companies Act 1966; or is placed under the Official Receiver and Manager (Receiver & Manager); or the developer is unable to acknowledge in writing to the Controller of Housing; Authorized and abandoned projects by the Ministry of Housing and Local Government under section 11 (1) (c) of Act 118. Although many solutions have been put forward and implemented, but statistics of abandoned construction projects remains in a state that ails. For example in Selangor, so far in 2014, there were 122 abandoned housing projects have been listed. Among the main problem raised when the issue was highlighted was the lack of money as an allowance for completing the project. With this occurrence, it has an impact on not only the buyer immediately but also other project players and the public. By its relatively limited research on this issue, a study was conducted to investigate the problem. Among the studies undertaken is to investigate the cause of this problem, thus providing questionnaires to architects, developers, property consultants, honorary general secretary, National House Buyers Association and others to seek the views and detailed information from third parties who are experienced in the industry on causes and ways how to solve this problem. A questionnaire survey was conducted to identify the significant factors that contribute to the abandoned housing in order to avoid or minimize this problem on construction project. The perspective of contractors, consultants and client has been analysed and ranked based on Relative Important Index (RII). Respondents believe that ‘delay in contractor’s payments to subcontractors’, ‘delay the timing of payments for completed work’ and ‘increases in project cost may be due to mismanagement or unfavourable economic conditions’ are the major factors that contributes in financial problems of abandoned housing in construction project. Finally, they are agreed that ‘encouraging project delivery success through some approaches such as public-private partnerships’ and ‘rehabilitation (reviving) of current abandoned project’ can help to minimize this problem.